Analisis Komposit Dengan Penguat Serat Enceng Gondok 40% Dan Serbuk Kayu Sengon 60% Pada Fraksi Volume 40%, 50%, 60% Bermatrik Resin Polyester Untuk Panel Akuistik - Nugroho, Tri Martanto Adi; , Wijianto, ST, M.Eng, Sc; , Supriyono, ST, MT, Ph.D (2016)
The research on the composite with reinforcements of Eichhornia crassipes fiber and sawdust aimed to knowing the tensile strength, bending, sound absorption, and describing the macro image of the results from the tensile testing and the bending testing of the volume fraction 40%, 50%, 60%. The early process was taking the Eichhornia crassipes stems then continued with drying them under the sun for about 10 days untill really dry, after that planed them using a wire brush till the fiber was separated from the leather of Eichhornia crassipes. The making of specimen used the method of Hand Lay-up, with a comparison of 40% Eichhornia crassipes fiber and 60% Albizia Chinensis sawdust using polyester resin of 157 BQTN Series. The processes of testing were the tensile testing which used ASTM D638-02 Standard, the bending test which used ASTM D790-02 Standard, and the sound absorption which used ANSI S1-13 Standard test with the volume fraction 40%, 50%, 60%. The result of the tensile testing of composite with the volume fraction 40%, 50%, 60% revealed that the average maximum tensile strength in the composite of the volume fraction 60% is as much as 15,883 N/mm2 and the smallest average tensile strength in the volume fraction 40% is as much as 9,736 N/mm2. In the bending test of the composite of the volume fraction 40%, 50%, 60%, the average maximum bending strength in the composite of the volume fraction 60% is as much as 31,438 Mpa and the smallest average bending strength in the volume fraction 40% is as much as 22,774 Mpa, and the results of the sound absorption test on the composite of Eichhornia crassipes fiber revealed that the highest absorption power in the volume fraction 60% is as much as 10,03 dB, and lowest absorption power was in the volume fraction 50%. In the macro image of the tensile testing and the bending test, the fracture structure of composite specimen was billow and irregular. In the volume fraction 40%, 50%, 60%, a process of enlargement of void and pull-out fiber dominated much.